Towards improved monitoring of offshore carbon storage: A real-world field experiment detecting a controlled sub-seafloor CO2 release. (March 2021) - Flohr, Anita; Schaap, Allison; Achterberg, Eric P.; Alendal, Guttorm; Arundell, Martin; Berndt, Christian; Blackford, Jerry; Böttner, Christoph; Borisov, Sergey M.; Brown, Robin; Bull, Jonathan M.; Carter, Liam; et al.
Highlights: The STEMM-CCS project completed a unique field experiment in the central North Sea. The experiment mimicked a leakage of CO2 from an offshore storage site. A custom setup released CO2 into shallow sediment at relevant leakage rates. Diverse established methods and novel technologies characterised the CO2 . The outcomes show such a release can be detected, attributed, and quantified. Abstract: Carbon capture and storage (CCS) is a key technology to reduce carbon dioxide (CO2 ) emissions from industrial processes in a feasible, substantial, and timely manner. For geological CO2 storage to be safe, reliable, and accepted by society, robust strategies for CO2 leakage detection, quantification and management are crucial. The STEMM-CCS (Strategies for Environmental Monitoring of Marine Carbon Capture and Storage) project aimed to provide techniques and understanding to enable and inform cost-effective monitoring of CCS sites in the marine environment. A controlled CO2 release experiment was carried out in the central North Sea, designed to mimic an unintended emission of CO2 from a subsurface CO2 storage site to the seafloor. A total of 675 kg of CO2 were released into the shallow sediments (∼3 m below seafloor), at flow rates between 6 and 143 kg/d. A combination of novel techniques, adapted versions of existing techniques, and well-proven standard techniques were used to detect, characterise and quantify gaseous and dissolved CO2 in the sediments and the overlying seawater. This paper provides an overview of this ambitious field experiment. We describe the preparatory work prior to the release experiment, the experimental layout and procedures, the methods tested, and summarise the main results and the lessons learnt.